Improving Self-Perceived Emotional Intelligence in Occupational Therapy Students Through Practical Training - Polonio-López, Begoña; Triviño-Juárez, José Matías; Corregidor-Sánchez, Ana Isabel; Toledano-González, Abel; Rodríguez-Martínez, Mª Carmen; Cantero-Garlito, Pablo; López-Martín, Olga; Rodríguez-Hernández, Marta; Segura-Fragoso, Antonio; Romero-Ayuso, Dulce María (Frontiers in Psychology, 2019)
Background: In the field of healthcare, higher skills in emotional intelligence (EI) have been proven to have a positive impact on healthcare professionals in general and occupational therapists in particular and also on teamwork and patient care. The purpose of this research was to determine whether performing practical work included in the undergraduate Occupational Therapy program improves students’ self-perceived EI, and whether there are any differences in the latter depending on the area in which this practical training is performed. Methods: It was conducted a multicenter, quasi-experimental, pre-post study with Occupational Therapy undergraduate students in the 2016-2017 academic year. A total of 184 students met the inclusion criteria. Of these, 10 (5.40%) declined to participate; therefore, the participation rate was 94.60% and the initial sample comprised 174 students. Mean age was 21.34 years (SD = 2.54) and 84.50% (n = 147) were women. Students’ self-perceived EI was measured with the Trait Meta-Mood Scale-24 (TMMS-24). This measure was completed in the two weeks prior to the start of the practical training period and one week after the end of it. McNemar-Bowker and McNemar tests were used to analyze the differences in self-perceived EI between these two points in time. Results: After the practical training, an improvement in self-perceived EI was observed in women (Emotional Attention, Emotional Clarity, and Emotional Regulation dimensions). Regarding areas of practical training, results showed an improvement in EI in women who had received practical training in the areas of Physical Rehabilitation, Mental Health and Geriatrics and Gerontology. Conclusions: The findings contribute to a better understanding of the relation between practical training and an improvement in self-perceived EI. This insight can help make changes in the teaching methodology to enhance the emotional skills needed for a better professional performance.